Assessment of the Prevalence of Markers of Monoinfection with Hepatitis C Virus and Coinfection with Hepatitis C and B Viruses among the Personnel of Medical Institutions of an Endemic Region - M. P. Kostinov; N. A. Magomedova; I. A. Khrapunova; A. V. Linok; E. Yu. Malinnikova; G. I. Alatortseva; L. N. Pritvorova; L. N. Nesterenko; I. I. Amiantova; V. V. Dotsenko; V. Yu. Kabargina; V. B. Polishchuk; et al. (Эпидемиология и вакцинопрофилактика)
Relevance. Parenteral viral hepatitis B (HBV) and C (HCV) affect not only millions of people, but also healthcare workers due to professional contacts, which lead to the progression of liver pathology and a reduction in medical activity. Numerous studies have shown that patients with double infection are at greater risk of developing progressive liver disease, cirrhosis, and hepatocellular carcinoma compared to monoinfected patients.Aim. To assess the characteristics of the spread of latent forms of hepatitis C monoinfection and hepatitis C and B coinfection among healthcare workers depending on age and medical specialty.Materials and methods. A serological and epidemiological observational descriptive prospective study was conducted based on the analysis of the results of a study of 1,643 workers who were considered healthy and did not have documented HBV, HCV, from 3 inpatient and outpatient medical organizations in an area with an active course of epidemic processes. Employees who were initially vaccinated against HBV were 1,597 (97.2 %) people and 46 (2.8 %) people who were not vaccinated. Subjects are included in the study after receiving written consent. Antibody levels were assessed based on the аnti–HВsAg study using commercial ELISA kits "VectoHBsAg - antibodies" (Russia); the presence of antibodies to the nuclear antigen of hepatitis B virus (anti- НВс) by the HepaBest anti-HBc-IgG ELISA method (Russia); the presence of total antibodies to HCV-core and -NS by the ELISA method «HCV-AT Confirmatory» (Russia). Statistical processing and analysis of the research results were carried out using Microsoft Excel 2010 and Prism9 software (GraphPad, USA.Results and discussion. For the period under review (2023-2024) In the structure of HCV cases, 5 % of the study sample (1,643) were young people (up to 44 years old), while elderly and middle-aged people (45-60 years old) were more susceptible to combined forms of HCV and HBV (1.7 %). In the structure of professional categories suffering from HCV, the main share belongs to the nursing staff - 45.1 % (p<0.001), and the shares of doctors and junior medical staff accounted for approximately 25 % of the total structure (p=0.999), which can be explained by the peculiarities of the HCV factor in the professional environment, namely more frequent It is the average medical staff who has contacts with the blood of patients. Among people with simultaneous positive biotests to the HCV and HBV nuclear antigen, the leading position was occupied by junior staff (nurses) – 35.7 %. The average age of this cohort is 52 years ±12.44 years, and 9 out of 10 people in this cohort are nurses who work in the same medical institution.Conclusion. The analysis makes it possible to identify organizations at the place of suspected infection, identify ways and factors of transmission, take measures to eliminate violations of the anti-epidemic regime, leading to increased risks of infection, and thereby ensure the biosafety of working conditions for healthcare workers.